Guilt and Madness in Edgar Alan Poe's "The Tell-Tale Heart”: Psychoanalysis Study - Rista Nur Kholifah; Aulia Sahda Rahima; Nurhabibah Qurrotul 'Aini; Hidayatul Nurjanah (Wanastra: Jurnal Bahasa dan Sastra, 2024)
Human being has different emotions within themselves, like sadness, happiness, upset and including guilt which can come from various causes. Uncontrolled guilt can be one of the causes of someone experienced madness, which then has a bad impact on themselves and other parties because this emotion of madness can lead someone to act beyond the reason. Guilt and madness can be found in the behavior of someone who is experiencing a bad psychological condition on the daily life. Guilt and madness can also be found in the literary works and one of them is from Edgar Allan Poe with a short story entitled The Tell-Tale Heart. This is a classic of the Gothic fiction genre that uses point of view from an unnamed narrator who experienced the guild and madness that lead the narrator to killed someone. Therefore, this research is intended to examine the feelings of guilt and madness that presented in the short story The Tell-Tale Heart by Edgar Allan Poe. This research uses qualitative methods and uses Sigmund Freud's 1923 psychoanalytic theory. This research conduct to reveals the relationship between guilt, madness, and the narrator's id in The Tell-Tale Heart short-story. Researchers found that “Ego” was more dominant from guilt and madness. This finding offers a new perspective on how guilt and madness are presented in Edgar Allan Poe's short story The Tell-Tale Heart seen from psychoanalytic theory which has the potential to provide input for future field research and practice.